2015
DOI: 10.1007/s10195-015-0360-0
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of proximal inter-phalangeal joint for hammertoe: intramedullary device options

Abstract: BackgroundProximal inter-phalangeal (PIP) joint arthrodesis today represents the standard treatment for structured hammertoes; however, recently, a lot of new intramedullary devices for the fixation of this arthrodesis have been introduced. The purpose of this work is to look at the currently available devices and to perform a review of the present literature. Materials and methodsA literature search of PubMed/Medline and Google Scholar databases, considering works published up until September 2014 and using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
(38 reference statements)
1
9
0
2
Order By: Relevance
“…Furthermore, the lack of rotational stability with K-wire fixation with only 1 wire can lead to malalignment, relapse of deformity, and a need for revision surgery. 21,24 The pain VAS mean score of 0.4 at the 26-week follow-up also compares well with studies of other implants. 2,39 In a retrospective comparative study of PIP joint fusion for correction of hammertoe deformity, Richman et al 39 reported mean pain VAS scores of 1.7 and 1.8 at the 12-month follow-up for 1-piece implant (n¼54) and K-wire (n¼95) fixation, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, the lack of rotational stability with K-wire fixation with only 1 wire can lead to malalignment, relapse of deformity, and a need for revision surgery. 21,24 The pain VAS mean score of 0.4 at the 26-week follow-up also compares well with studies of other implants. 2,39 In a retrospective comparative study of PIP joint fusion for correction of hammertoe deformity, Richman et al 39 reported mean pain VAS scores of 1.7 and 1.8 at the 12-month follow-up for 1-piece implant (n¼54) and K-wire (n¼95) fixation, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…14 Kirschner wire (K-wire) fixation is considered the standard treatment for correction of hammertoe deformity. 21,28,44 Although inexpensive and easy to insert, percutaneous K-wires protrude from the toe during the initial 6-week recovery period and require removal. 24 Complications include wire site infection, wire migration, wire breakage, and nonunion or malunion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10,11 Complications of using axial K-wires in joint fixation may develop, including inconvenience, pin-tract infection, wire migration, and hardware failure especially since there is no compression or rotational stabilization in axial K-wires. 11 Several alternative options have appeared in recent years, 12 such as the Smart Toe (Stryker Corporation), [13][14][15] TenFuse (Wright Medical Group), 16 StayFuse (Tornier), 17 Hat-trick (Smith and Nephew), and HammerFix (Extremity Medical). These internal fixation methods aim to reduce K-wire complications and aim to achieve a higher level of patient satisfaction, pain control, and union rates.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,[17][18][19] However, the high cost of these novel internal devices is one of the major reasons hindering more universal utilization. 12 The purpose of this study is to compare the surgical outcomes of K-wire fixation versus novel internal fixation devices in PIPJ arthrodesis in hammer toe surgery.…”
Section: Introductionmentioning
confidence: 99%